Transmission of Ovine Herpesvirus 2 in Lambs - Li, Hong (American Society for Microbiology, 1998)
The pattern of acquisition of ovine herpesvirus 2 (OHV-2) infection in lambs was examined by a competitive-inhibition enzyme-linked immunosorbent assay and PCR. Newborn lambs (n = 118) did not exhibit antibody at birth. Viral DNA in peripheral blood leukocytes was detected in only 3% (n = 77) of newborn lambs before suckling. After nursing, viral DNA was sporadically present in about 10 to 20% of lambs until about 3 months of age. Thereafter, strong DNA signals began to appear in increasing numbers of lambs, reaching 100% by 5.5 months of age. Viral DNA in nasal secretions began to be detectable in about 30% of lambs at 5.5 months of age, achieved significant levels in 88% of lambs by 7.5 months of age, and then declined. The kinetics of the humoral immune response in lambs paralleled those of viral DNA in nasal secretions but did not parallel its presence in blood leukocytes. In the experiment to define the time of infection of OHV-2 in lambs, all five lambs separated from the flock at 2.5 months of age remained uninfected until the termination of the experiment at 1 year of age. In contrast, lambs weaned at 2.5 months of age and returned to the flock had become infected at 3.5 months of age. Weaning and separation from the flock at 3.5 months of age did not prevent infection. The study showed that OHV-2 infection does not commonly occur in perinatal lambs and that OHV-2-free sheep can be established by separation of lambs at the proper time, which has important implications for potential control measures.